1999
DOI: 10.1093/tropej/45.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Radiological analysis of children with cystic fibrosis who are homozygous for cystic fibrosis transmembrane conductance regulator mutation S549R (T->G)

Abstract: Genotype-phenotype analyses in cystic fibrosis (CF) have shown that cystic fibrosis transmembrane conductance regulator (CFTR) genotypes can predict pancreatic status but that correlations with pulmonary status remain elusive. We investigated the extent and severity of lung disease associated with CFTR mutation S549R (T-->G). This mutation is localized in intron 11 (nucleotide-binding fold 1 of the CFTR protein) and had so far been described as a private mutation only. It is associated with an extremely severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, although a patient with an R1158X/S549R(T→G) genotype could have been expected to present with severe clinical manifestations, we find here that it is not the case. The fact that the Emirati patient investigated here lives in the same environmental and medical conditions as the subjects that we have studied before [4–6] prompts us to believe that there must be attenuating genetic factors. Indeed, Duarte et al [9] have reported that a complex allele containing two mutations, R334W and R1158X, is associated with reduced levels of correctly processed mRNA, and that a patient with the complex genotype R334W–R1158X/ΔF508 presented with pancreatic sufficiency and an atypical course of CF.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, although a patient with an R1158X/S549R(T→G) genotype could have been expected to present with severe clinical manifestations, we find here that it is not the case. The fact that the Emirati patient investigated here lives in the same environmental and medical conditions as the subjects that we have studied before [4–6] prompts us to believe that there must be attenuating genetic factors. Indeed, Duarte et al [9] have reported that a complex allele containing two mutations, R334W and R1158X, is associated with reduced levels of correctly processed mRNA, and that a patient with the complex genotype R334W–R1158X/ΔF508 presented with pancreatic sufficiency and an atypical course of CF.…”
Section: Discussionmentioning
confidence: 91%
“…We had so far observed that, in the UAE, mutations ΔF508 and S549R(T→G) account for 88% of CF chromosomes, and that CF patients were homozygous for either of the two mutations – a phenomenon that reflects the high level of consanguinity among Emirati [4]. Moreover, the clinical phenotypes associated with both mutations are quite homogeneous and extremely severe [5], including dramatic losses of pulmonary function [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation